CORPORATE TAX MANAGEMENT BEHAVIOUR DURING INITIAL PUBLIC OFFERING PROCESS: EVIDENCE FROM INDONESIA - Pamungkas, Dikdik; Tanzil, Nanny; Kasma, Juan (TRIKONOMIKA, 2025)
Tax management refers to strategies employed by companies or individuals to manage tax obligations efficiently, particularly during the Initial Public Offering (IPO) process. Corporate tax management behavior is measured using the Effective Tax Rate (ETR). This study uses secondary data from 78 companies that conducted IPOs in 2023 and published prospectus reports for three years prior to the IPO. Panel data regression with the Common Effect Model (CEM) is applied for analysis. The findings indicate significant changes in corporate tax management behavior during the IPO process. Leverage, firm size, profitability, and auditor changes positively influence tax management practices, while investment bank reputation has a negative effect. The study concludes that higher leverage, larger firm size, and greater profitability are associated with lower ETRs, indicating more aggressive tax management, whereas reputable investment banks tend to reduce such aggressive behavior.